Preliminary Study on Teachers' Use of the iPad in Bachelor of Education Program at a Private University in Malaysia - Yusup, Hashim (International Electronic Newsletter, 2014)
In March 2011, 97 teachers registered at a private Malaysian university where each of them was given a 1st generation iPad tablet to assist them in their studies. The university practices blended learning, which combines face-to-face interaction with online learning using mobile technologies. At that moment, it is the only university that provides iPad tablets to teachers in the Teacher Education Graduating program. !